Effects of COVID-19 on bone fragility: a new perspective from osteoimmunological biomarkers - Galliera, Emanuela; Massaccesi, Luca; Mangiavini, Laura; De Vecchi, Elena; Villa, Francesca; Corsi Romanelli, Massimiliano Marco; Peretti, Giuseppe (Frontiers in Immunology, 2024)
While there is an increasing understanding of COVID-19's effect on different organs, little is known about the effect of the disease on bone turnover and remodeling so far. Osteoimmunological biomarkers have been described as potential indicators of bone remodeling in inflammatory conditions, but their potential role in evaluating the effect of COVID-19 on bone fragility has not been explored so far. The present study aims to measure the osteoimmunological biomarkers in elderly patients undergoing orthopedic surgery, to evaluate the potential effect of COVID-19 on the bone response to the surgery. In our patients, the RANKL/OPG ratio indicated an increase of bone resorption in COVID-19-positive patients, confirming a strong diagnostic and prognostic value. RANKL/OPG displays a good correlation with the bone fragility maker FGF23, indicating that this parameter is a reliable maker of bone fragility in COVID-19 patients and could provide useful and comprehensive information about inflammation-induced bone loss. Consistently, the RANKL/OPG ratio showed a good correlation also with the two inflammatory markers IL-6 and sRAGE. Taken together these results indicate that the use of an osteoimmunological biomarker like the RANKL/OPG ratio could provide a significant improvement in the clinical evaluation of the COVID-19 effect on bone loss. This aspect is extremely important in elderly patients undergoing orthopedic surgery, which can manifest more severe effects of COVID-19 and present an increased level of age-induced bone fragility.